Comparison of the pharmacokinetic variations of different concentrations of ropivacaine used for serratus anterior plane block in patients undergoing thoracoscopic lobectomy: a population pharmacokinetics analysis - Ling, Jing; Xu, Caomei; Tang, Lingkai; Qiu, Lan; Hu, Nan (Frontiers in Pharmacology, 2025)
ObjectiveRopivacaine serratus anterior plane block is widely used in clinical analgesia in patients undergoing thoracoscopic surgery. Different concentrations of ropivacaine have different analgesic effects, and the safety is highly correlated with the plasma concentration. In this study, the nonlinear mixed effects modeling (NONMEM) method was used to investigate the population pharmacokinetics (PPK) characteristics of ropivacaine and explored the relationship between the covariates on the pharmacokinetic parameters of ropivacaine, in order to provide a theoretical basis for the rational use of ropivacaine.MethodsThis study was approved by the Ethics Committee of the First People’s Hospital of Changzhou. The informed consent of patients was obtained. A total of 43 patients who underwent thoracoscopic pneumonectomy in our hospital from April to December 2023 were included. Patients were randomly assigned to four ropivacaine concentration groups of 0.25%, 0.375%, 0.5%, and 0.75%, respectively, and administered with a dose of 3 mg/kg. Arterial blood was taken at 1, 15, 30, 45 min, 1, 2, 4, 8, 12, and 24 h after ropivacaine administration through superficial serratus anterior plane block. The concentration of ropivacaine was detected by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The PPK model was constructed by NONMEM. The final model was verified by using the goodness of fit, visual predictive check (VPC) and normalized predictive distribution error (NPDE). Monte Carlo simulation was applied to evaluate and optimize the dosing regimens.ResultsA total of 388 plasma concentration data from 41 patients were used to establish the model. Eighteen blood concentrations from the other two patients were used for external validation. A two-compartment with zero-order and first-order mixed absorption model was the best model. The proportion of zero-order absorption was 27.4%, the absorption time of zero-order absorption was 0.49 h and the zero-order absorption infusion time was 0.015 h. The first-order absorption rate constant (ka)was correlated with the concentration of ropivacaine. The ka of ropivacaine were 32.0, 19.4 and 14.4 h−1 for 0.25%, 0.5%, and 0.75% ropivacaine, respectively, which indicating that the peak time (Tmax) of low-concentration ropivacaine was significantly shortened. Other pharmacokinetic parameters results were as follows: CL/F(L/h) = 7.475, Vc/F(L) = 125, Q/F(L/h) = 14.7, Vp/F(L) = 197. In addition, the platelet count has an effect on the Vc/F. The simulation results demonstrate the total dose of ropivacaine is recommended not to exceed 300 mg to avoid the occurrence of adverse reactions.ConclusionThis is the first population pharmacokinetic study of ropivacaine superficial serratus anterior plane block in patients undergoing thoracoscopic pulmonary resection. The model exhibits excellent stability and reliability, thereby offering valuable insights into personalized clinical drug administration. The concentration of ropivacaine and platelet count have significant impacts on the pharmacokinetic parameters of ropivacaine.